Specific Primer Design for Detection and Quantification of Entomopathogenic Fungi Metarhizium anisopliae using Quantitative PCR (qPCR) in Soil and Cocoon Samples - Saragih, Syaiful Amri; Takemoto, Shuhei; Kamata, Naoto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
The information on the abundance and dynamics of entomopathogenic fungus Metarhizium anisopliae on the soil is limited by the existence of insect hosts. In this study, to detect and quantify specifically for M. anisopliae from extract of soil DNA, a culture-independent approach based on DNA and employing quantitative Polymerase Chain Reaction (qPCR) was developed. Primer pairs were designed and tested for their specificity to get a specific primer pair. The best primer pair was determined to be MA6071F/MA6218R. Two standard curves were created using 10 concentration levels (101 to 1010) by qPCR. Standard curves for genomic DNA showed a strong relationship and good fitting (R2 > 0.980). Six levels were obtained to generate standard genomic DNA (R2= 0.98, E = 1.05). Eight levels (R2= 0.9854, E = 0.91) were created for standard soil DNA. By qPCR, M. anisopliae was not found in all soil samples, possibly due to the samples' low fungal density. However, 13 dead cocoon samples out of 80 showed positive for M. anisopliae. To successsfully detect and quantify M. anisopliae in soil, the method of DNA extraction and soil sampling should be enhanced.